Reconfigurações industriais das regiões metropolitanas do Nordeste: uma análise a partir do emprego formal - Brandão, Danilo Duarte (2013)
Industrial development experienced by Brazil from the 1950s, changed the concentration of population in the country. The process of development of domestic industry, concentrated in urban areas, crowded growing portion of the population.The Southeast region during the first stage of industrialization driven by the state, with the implementation of Plan goals, captained the major industrial projects implemented in the period and became the main industrial center of the country.In the decade from 1960 to 1980 the state action was marked by numerous regional development projects, softening the industrial concentration and Brazilian investment redirected to the Northeast.The second National Development Plan implemented in the 1970s led to major investments Northeast.This period marked the widespread urban growth and institutionalization of the first metropolitan areas in Brazil.The change of this developmental process is altered with the fiscal and financial crisis of the state in the 1980s and 1990s and spending cuts aimed at national development, reorienting the economy to liberal policies of economic liberalization and reduction of activity in the economy.Industrial policy was relegated to local development plans from the 1990s to the federating units fitting the wide use of tax incentives, the "war tax" to the continued industrialization process.In this context of the national economy work seeks to analyze the industrial setting in the metropolitan areas of Fortaleza, Recife and Salvador between 1995 and 2010.Although the metropolitan areas of Fortaleza, Recife and Salvador are the main urban centers of the Northeast, responsible for the advancement of industrial development, reconfigurations occurred between 1995 and 2010 by changing the level of industrial specialization built by regional division of labor in these regions.The work will be carried out by the method of descriptive analysis of the literature review on regional and urban development.Constitute quantitative method as the secondary data analysis of formal employment from the Annual Social Information (RAIS) Ministry of Labour and Employment (MTE).Using data RAIS / MTE analyzes the industrial specialization index using the Locational Quotient (LQ).Thus, it is assumed as a parameter analysis QL> 1, when the region has become specialized in a particular sector or QL <1, when the region does not have expertise in industrial sector analyzed.The conclusion of study indicates that there was in these metropolitan areas maintained the same bias hub.Fiscal policies, the states, was not successful in diversifying the productive structure and the Northeast region itself.This result is demonstrated by the need and dependence on state investments in the region to promote development.Industrial policies of recent years have been positive to meet the objectives of employment generation, but there must be specific policies for better diversification of production, in addition to integrating the economy of the Northeast sector and regionally